Bone Mineral Density across the Lifespan in Patients with Type 1 Diabetes - Halper-Stromberg, Eitan (J Clin Endocrinol Metab, 2019)
CONTEXT: Fracture risk in people with type 1 diabetes (T1D) is higher than their peers without diabetes. OBJECTIVE: To compare bone mineral density (BMD) across the lifespan in individuals with T1D and age- and sex-matched healthy controls. DESIGN: Cross-sectional. SETTING: Subjects (5–71 years) with T1D and matched controls from ongoing research studies at Barbara Davis Center for Diabetes. PATIENTS OR OTHER PARTICIPANTS: Participants with lumbar spine BMD by dual X-ray absorptiometry (DXA) were divided into 2 groups: children ≤20 years and adults >20 years. INTERVENTION: None. MAIN OUTCOME MEASURES: Comparison of BMD by diabetes status across age groups and sex using a linear least squares model adjusted for age and body mass index (body mass index (BMI) for adults; and BMI z-score in children). RESULTS: Lumbar spine BMD from 194 patients with T1D and 156 controls were analyzed. There was no difference in age- and BMI-adjusted lumbar spine BMD between patients with T1D and controls: among male children (least squares mean ± standard error of the mean [LSM ± SEM]; 0.80 ± 0.01 vs 0.80 ± 0.02 g/cm(2), P = .98) or adults (1.01 ± 0.03 vs 1.01 ± 0.03 g/cm(2), P = .95), and female children (0.78 ± 0.02 vs 0.81 ± 0.02 g/cm(2), P = .23) or adults (0.98 ± 0.02 vs 1.01 ± 0.02 g/cm(2), P = .19). Lumbar spine (0.98 ± 0.02 vs 1.04 ± 0.02 g/cm(2), P = .05), femoral neck (0.71 ± 0.02 vs 0.79 ± 0.02 g/cm(2), P = .003), and total hip (0.84 ± 0.02 vs 0.91 ± 0.02, P = .005) BMD was lower among postmenopausal women with T1D than postmenopausal women without diabetes. CONCLUSION: Across age groups, lumbar spine BMD was similar in patients with T1D compared with age- and sex-matched participants without diabetes, except postmenopausal females with T1D had lower lumbar spine, femoral neck, and total hip BMD.